(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Jwara appears as an independent disease and also as a Lakshana of various diseases. Because of this, it is the common health problem met within medical practice. That is why, Ayurveda gives much importance to Jwara and considered Jwara as Sarvarogaadhipati. Abnormal food habits, style of living etc. factors disturb Jatharagni and health, which leads to Jwara and Vedana. Srirama Rasa is a unique herbo-mineral formulation explained in the Jwara Chikitsa Prakaranam of Bhaishajya Ratnavali having a multi- dimensional therapeutic action i.e., Ama jwara, Shoola, Vishtambha and Vata vikaras. It is a potent formulation having Shuddha Parada, Shuddha Gandhaka, ShuddhaJayapala Beeja and Maricha given Bhavana with Dantimoola kwatha. Methodology: Raw materials were screened and collected and the formulation selected for the present study Srirama Rasa was prepared accordingly. Experimental study was conducted in 3 group of animals for Anti-pyretic study. Anti-pyretic study was done by Yeast induced pyrexia method in Albino rats. Results: In Anti-pyretic study, a significant result was observed in standard group and trial group. But in standard group, it was more significant than control & trial group. In trial drug, a significant decrease in rectal temperature was observed from 5th to 6th hr, while in standard group it was from 2nd to 6th hr. Conclusion: Srirama Rasa has demonstrated significant Anti-pyretic activity. This study has provided evidence base and given scope for clinical research.